2015
DOI: 10.1021/am508569m
|View full text |Cite
|
Sign up to set email alerts
|

Controlled van der Waals Epitaxy of Monolayer MoS2 Triangular Domains on Graphene

Abstract: Multilayered heterostructures of two-dimensional materials have recently attracted increased interest because of their unique electronic and optical properties. Here, we present chemical vapor deposition (CVD) growth of triangular crystals of monolayer MoS2 on single-crystalline hexagonal graphene domains which are also grown by CVD. We found that MoS2 grows selectively on the graphene domains rather than on the bare supporting SiO2 surface. Reflecting the heteroepitaxy of the growth process, the MoS2 domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
111
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 50 publications
14
111
0
1
Order By: Relevance
“…[ 21 ] Alternatively, Ago et al demonstrated the van der Waals epitaxy of monolayer MoS 2 on transferred Gr domains (from Cu foils) on SiO 2 /Si by using MoO 3 and S precursors. [ 22 ] To avoid the Gr sample transfer, Zhang et al [ 23 ] and Huang et al [ 24 ] subsequently synthesized monolayer MoS 2 directly on the bulk state of Gr, mainly toward investigating the metallic edge state and bandgap tunability at the domain boundary of MoS 2 by employing scanning tunneling microscopy and spectroscopy (STM/STS). However, the effects of Gr on MoS 2 mainly regarding the bandgap tunability and doping effect, etc., still can not be resolved on these heterostructures systems.…”
Section: Doi: 101002/adma201503342mentioning
confidence: 99%
“…[ 21 ] Alternatively, Ago et al demonstrated the van der Waals epitaxy of monolayer MoS 2 on transferred Gr domains (from Cu foils) on SiO 2 /Si by using MoO 3 and S precursors. [ 22 ] To avoid the Gr sample transfer, Zhang et al [ 23 ] and Huang et al [ 24 ] subsequently synthesized monolayer MoS 2 directly on the bulk state of Gr, mainly toward investigating the metallic edge state and bandgap tunability at the domain boundary of MoS 2 by employing scanning tunneling microscopy and spectroscopy (STM/STS). However, the effects of Gr on MoS 2 mainly regarding the bandgap tunability and doping effect, etc., still can not be resolved on these heterostructures systems.…”
Section: Doi: 101002/adma201503342mentioning
confidence: 99%
“…Therefore considerable efforts are required for scalable synthesis of p-type MoS 2 film to realize practical applications. To date, a direct growth method of MoS 2 thin films by chemical vapor deposition (CVD) via vapor-phase reaction of MoO 3 and sulfur (S) powders, [18][19][20][21] MoCl 5 and S powders, 22,23 and metal Mo films [24][25][26][27][28] in a CVD furnace have been demonstrated to overcome a large area film synthesis. Among them, the direct grown method of TMDs (e.g.…”
mentioning
confidence: 99%
“…To resolve such issues, Tsuji et al, presented APCVD growth of triangular MoS 2 flakes on the APCVD-derived, single-crystalline monolayer hexagonal Gr domains transferred on SiO 2 /Si substrates. [60] They found that monolayer MoS 2 selectively nucleated on the Gr domains rather than on the bare supporting SiO 2 surfaces, thus indicating a heteroepitaxy growth mechanism. Meanwhile, the MoS 2 domains revealed two preferred equivalent orientations (SEM image in Figure 8b).…”
Section: Cvd Syntheses Of MX 2 /Gr Heterostructuresmentioning
confidence: 99%
“…The photo-induced electron transfer from monolayer MoS 2 to Gr and the optical memory effect were also demonstrated in the MoS 2 /Gr vertical heterostructures. [60] Subsequently, Alem et al, reported the syntheses of nearly freestanding MX 2 /Gr heterostructures on Quantifoil TEM grids with ≈2 μm holes by the APCVD growth of monolayer MX 2 on transferred monolayer Gr (from Cu foils) (Figure 8c). [127] Notably, this work enabled the on-site investigation of the growth dynamics of MX 2 on Gr surfaces at an atomic resolution.…”
Section: Cvd Syntheses Of MX 2 /Gr Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation